Bullet Journal for mental health self-care: the role of Information Design - Almeida da Silva, Naira; Tiradentes Souto, Virgínia; Mansur de Oliveira, Ana (InfoDesign, 2025)
The Bullet Journal method is an information management tool based on information design strategies. It was developed to manage personal information and improve overall well-being in everyday life. This exploratory study examines the role of information design in the use of the bullet journal for mental health self-care using the Grounded Theory Method in online sources where users share their practices. We discuss the four usage trends identified: Self-Regulation Resources, Self-Regulation Exercises, Psychological Aspects Trackers, and Psychoeducation. The method’s flexibility allows users to adapt layouts according to their needs and contexts, supporting self-awareness, emotional regulation, and self-expression. By creating personalized visual systems, individuals actively participate in their mental health care, supporting their autonomy.